2021
DOI: 10.3390/ijms222313048
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of SRO Gene Family in Sesamum indicum (L.) Reveals Its Association with Abiotic Stress Responses

Abstract: SIMILAR TO RCD-ONEs (SROs) comprise a small plant-specific gene family which play important roles in regulating numerous growth and developmental processes and responses to environmental stresses. However, knowledge of SROs in sesame (Sesamum indicum L.) is limited. In this study, four SRO genes were identified in the sesame genome. Phylogenetic analysis showed that 64 SROs from 10 plant species were divided into two groups (Group I and II). Transcriptome data revealed different expression patterns of SiSROs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…It was reported that genes in SRO family play vital roles in the resistance to various abiotic stresses. In this work, many cis-elements responding to stresses (especially ARE and STRE) were distributed in the promoters of CsSRO genes (Figure 5), and similar results were reported in the promoter regions of SolySRO and SiSRO genes [46,50]. The qRT-PCR analysis also revealed that the expression of four CsSRO genes were significantly induced under salt and drought stress (Figure 7), suggesting their involvement in stress tolerance.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…It was reported that genes in SRO family play vital roles in the resistance to various abiotic stresses. In this work, many cis-elements responding to stresses (especially ARE and STRE) were distributed in the promoters of CsSRO genes (Figure 5), and similar results were reported in the promoter regions of SolySRO and SiSRO genes [46,50]. The qRT-PCR analysis also revealed that the expression of four CsSRO genes were significantly induced under salt and drought stress (Figure 7), suggesting their involvement in stress tolerance.…”
Section: Discussionsupporting
confidence: 82%
“…As shown in the phylogenetic tree, these SRO proteins were irregularly divided into two groups, namely group I and group II, and group I can be further divided into four subgroups (Ia to Id) (Figure 1). Consistent with previous reports [45,46], the SRO proteins of these species were clustered in dicot-or monocot-specific patterns. For example, group II had only dicotyledonous SRO proteins, while group I contained both monocotyledonous and dicotyledonous SRO proteins.…”
Section: Phylogenetic Analysis Of Sro Family Genes From Cucumber and ...supporting
confidence: 92%
See 3 more Smart Citations